Comparative Evaluation of the Fluoride Recharge Ability of Two Glass Ionomers Obtained from Fluoridated Dentifrice and CPP-ACFP Paste: An In-vitro Study - Karim Jafari; Saleh Hoseini; Somayeh Hekmatfar (Mashhad University of Medical Sciences, 2019)
Introduction: Glass ionomer cement (GIC) is a restorative material used in pediatric dentistry, which attaches to dental hard tissues and has cariostatic properties due to the ability for fluoride release. The present study aimed to assess the fluoride release and uptake capacity of two GICs in the presence of various fluoride sources. Methods: This in-vitro study was conducted on 120 disks composed of two GICs (Fuji II LC, Equia Forte System), which were prepared with the exact dimensions of 5×2 millimeters. Fluoride release ability of the samples was determined every 24 hours for seven days and weekly (days 7-21) using a combination of ion selective electrodes. The samples in each group were divided into three subgroups and subjected to no fluoride treatment, fluoridated dentifrice (once a day for one minute), and MI Paste Plus (once a day for one minute). After recharging the samples for seven days, the level of fluoride release was measured on days 1-7, 14, and 21. Results: The results of one-way analysis of variance indicated that the fluoride release ability of Fuji II was higher compared to that of EQUIA Forte (P